Histopathological Research of the Therapeutic Effects of Grape (Vitis vinifera L.) Seeds Extracts on Cadmium-Exposed Carp (Cyprinus carpio L. 1758) - Nuh Korkmaz (Turkish Journal of Agriculture: Food Science and Technology)
This study was designed to investigate the therapeutic effects of Vitis vinifera L. seed extract (5 ppm and 10 ppm) on gill and liver tissues histopathology of carp (Cyprinus carpio L. 1758) exposed to cadmium chloride (CdCl2=Cd) (20 ppb) acute and subchronic period. A total of 140 fish in 14 groups were used in the experiment. The experiment was designed as in two different periods (acute and chronic) and 7 different dose groups (control, vehicle, V. vinifera seed extract 5 ppm, V. vinifera seed extract 10 ppm, Cd 20 ppb, V. vinifera seed extract 5ppm + Cd 20 ppb and V. vinifera seed extract 10 ppm + Cd 20 ppb). At the end of the experiment, the gill and liver tissues dissected from the fish were fixed, dehydrated, cleared, and paraffin impregnated. Appropriately sized blocks were prepared from the tissues, sections of 5-7 µm thickness were taken and covered by staining with hematoxylin-eosin. Stained preparations were examined under a light microscope and photographed. It was determined that all dose groups in the acute period and control groups were not different histopathological. It was determined that the histopathological damage caused by the cadmium group in the subchronic period and tissue damage were reduced in the dose groups with cadmium added with V. vinifera seed extract. As a result of the study, it was concluded that V. vinifera seed extract could have a therapeutic effect on the gill and liver tissues of carp exposed to cadmium.